PENGARUH PEMBERIAN PUPUK ORGANIK GRANULTERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAILAN (Brassica oleracea. L ) DI POLYBAG - Meriyanto Toyib; Bastani Sepindjung; Astutini Sp (Universitas Tridinanti Palembang, 2016)
Effect of Organic Fertilizer on Growth and Yield kailan plants (Brassica oleracea.L) in polybags. This research is expected to be useful for science and technology, and canbe used as a guide for people who want to cultivate crops kailan. This research has beencarried out in the yard area Kertapati Palembang, starting in December 2014 to February2015. Research using experimental methods randomized block design (RBD) consistingof 6 treatments and each treatment was replicated 4 times. The treatment under study isthe application of fertilizer granules P1 = 125 g / polybag (5 ton / ha) P2 = 187.5 g /polybag (7.5 / ha), P3 = 250 g / polybag (10 tons / ha), P4 = 312.5 g / polybag (12.5 / ha),P5 = 375 g / polybag (15 tons / ha), P6 = 437.5 g / polybag (17.5 tons / ha). The variablesmeasured were: plant height (cm), stem diameter (cm), plant fresh weight (g) and plantdry weight (g). Based on the results of the study showed that the giving of granularfertilizer with a rate of 312.5 g / polybag or equal to 12.5 tons / ha gives a good effect onplant height, stem diameter, wet weight of plant, plant dry weight and leaf consecutive30.48 cm; 0.72 cm; 86.79 g; 8,73 g; 6.95 g and 881,82 cmÃ‚Â².Keywords : Kailan, organic fertilizer, growth and yield